ANALISIS PERJANJIAN PENGADAAN PAKAIAN DINAS MELALUI LELANG (STUDI PADA DINAS PENDAPATAN PROPINSI SUMATERA UTARA) - MEUTIA RAHMIYATI (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. Muhd Yamin3. Faisal Akbar Nasution The contract on the procurement of uniforms is part of the agreement between the Revenue Office of North Sumatera Province and the contractor to fulfill the need of uniforms the finance of which comes from APBD (Regional Budget). The method of procuring uniforms is done transparently by using wide-ranging announcement through mass media and on announcement boards at the Revenue Office of North Sumatera Province in order that business people who are interested in the tender and have met the qualification can participate in it. Basically, all procurements of uniforms are done through public auction so that there will be competitive auction which is aimed to get favorable price for all parties involved in the procurement of uniforms. The implementation of legal principle in auction agreement in the procurement of uniforms at the Revenue Office of north Sumatera Province is carried out by using the principle of transparency because in achieving the accountability, the principle of transparency must be implemented. Besides that, the Revenue Office of North Sumatera Province also applies the principles of efficiency, effectiveness, transparency, competitiveness, and fairness in procuring uniforms. The method of procuring uniforms at the Revenue Office of North Sumatera Province can also carried out by public auction which is aimed to obtain competitive auction which is expected to obtain the most favorable price of goods and service for the company.Keywords: Contract, Implementation, Procurement of Uniforms